2010
DOI: 10.1038/labinvest.2010.82
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor production by activated pancreatic stellate cells in mouse alcoholic chronic pancreatitis

Abstract: Alcoholic chronic pancreatitis (ACP) is characterized by pancreatic necrosis, inflammation, and scarring, the latter of which is due to excessive collagen deposition by activated pancreatic stellate cells (PSC). The aim of this study was to establish a model of ACP in mice, a species that is usually resistant to the toxic effects of alcohol, and to identify the cell type(s) responsible for production of connective tissue growth factor (CTGF), a pro-fibrotic molecule. C57Bl/6 male mice received intraperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…collagen) in a CCN2-dependent manner following ethanol exposure. Since we previously showed that activated PSC are the main producers of collagen and CCN2 in a mouse model of CP (Charrier and Brigstock 2010), the goal of the present study was to determine the action of miRs up-or down-stream of CCN2 during PSC activation. We initially performed a miR microarray on total pancreatic RNA collected from mice with ethanol-induced CP.…”
Section: Resultsmentioning
confidence: 99%
“…collagen) in a CCN2-dependent manner following ethanol exposure. Since we previously showed that activated PSC are the main producers of collagen and CCN2 in a mouse model of CP (Charrier and Brigstock 2010), the goal of the present study was to determine the action of miRs up-or down-stream of CCN2 during PSC activation. We initially performed a miR microarray on total pancreatic RNA collected from mice with ethanol-induced CP.…”
Section: Resultsmentioning
confidence: 99%
“…Examples are the fibroblast-growth factors -1 and -2 (FGF-1 and -2), IGF-1, connective tissue growth factor (CTGF), and EGF (7,8,10,14,23,25,39). Interestingly, the extent to which endogenous protective and injurious factors interact with each other has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although utilization of experimental models has helped identify molecular mechanisms linked to development of CP (19,32,41,47), significant gaps persist in our knowledge of endogenous factors that function to either inhibit or amplify the inflammatory-fibrosis cascade (7,9,41), a key component of the CP disease process.…”
mentioning
confidence: 99%
“…This signal increased the cell adhesion and migration of PSCs, leading to PSC activation [55]. CTGF was supplied from activated PSCs themselves, which were activated by exogenous stimulants such as ethanol [56]. Another report described that pancreatic cancer cells could also become a source of CTGF in pancreatic cancer tissue [57].…”
Section: Detailed Mechanism Of Psc Activation In Pancreatic Cancermentioning
confidence: 99%